Republic of Moldova - at the confluence between East and West - Cristian Caraman (CES Working Papers, 2017)
Recent developments in relations between the European Union and the Russian Federation are of major interest for the international community. The way in which the two will cooperate in the context of the Crimean crisis and in other issues related to the Eastern European space is very important not only for them, but also for the other countries, which are find themselves at the confluence between them, such as the Republic of Moldova. The role of the Republic of Moldova in securing stability and peace in the region is growing, and with it, the responsibility of the Moldovan authorities to manage their relations with the great powers is growing as well. The study aims to present the effect which the relations between Moldova and the great powers have on its economy and future political perspectives and their evolution in the context of recent events.
Keywords: 330; Eastern Europe; economy; relations; perspectives